The 4D pixel challenge. (7th December 2016) - Cartiglia, N.; Arcidiacono, R.; Bellora, A.; Cenna, F.; Cirio, R.; Durando, S.; Ferrero, M.; Freeman, P.; Galloway, Z.; Gruey, B.; Mashayekhi, M.; Mandurrino, M.; et al.
Abstract: Is it possible to design a detector able to concurrently measure time and position with high precision? This question is at the root of the research and development of silicon sensors presented in this contribution. Silicon sensors are the most common type of particle detectors used for charged particle tracking, however their rather poor time resolution limits their use as precise timing detectors. A few years ago we have picked up the gantlet of enhancing the remarkable position resolution of silicon sensors with precise timing capability. I will be presenting our results in the following pages.